Factors Related to Open Defecation Behavior Among School-Age Children in West Lombok - Makhfudli Makhfudli; Praba Diyan Rachmawati; Saskiyanti Ari Andini (Jurnal Ners, 2017)
Introduction: Open defecation behavior is one cause of poor sanitation, which can lead to various diseases. Open defecation behavior related with cultural factors that become a habit in the daily life in a society which was then followed by their children. This study aimed to analyze factors related to the parental behavior of open defecation in school-age children based on the theory of transcultural nursing in Marce, Sedau Community Health Center Area, West Lombok Indonesia Methods: This was a descriptive research design with cross-sectional approach. Samples were taken by simple random sampling technique and obtained 95 parents of children aged 7-12 years. Independent variables were education level, economy level, cultural values and lifestyle, social and family values, religiosity, technology. The dependent variable was open defecation behavior of the parents in school age children. This research was analyzed using Spearman rho test with significance level α = 0.05.Results: education level (p = 0.000; r = 0.390), economy level (p = 0.003; r = 0.298), cultural values and lifestyle (p = 0.000; r = 0.555), social and family (p = 0.000; r = 0.444), religiosity (p = 0.000; r = 0.300), technology (p = 0.000; r = 0354) has a significant relationship with the parents about the open defecation behavior in school age children.Conclusion: the intervention was needed on the factors that influence the open defecation behavior by nurses participating directly to communities to increase public awareness about the importance of healthy defecate in a closet to avoid the disease.